2014
DOI: 10.1620/tjem.232.69
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Pancreatitis: The 2014 Update

Abstract: Chronic pancreatitis is a progressive inflammatory disease in which pancreatic secretory parenchyma is destroyed and replaced by fibrous tissue, eventually leading to malnutrition and diabetes. Alcohol is the leading cause in Western countries, but genetic factors are also implicated. Since the identification of mutations in the cationic trypsinogen (PRSS1) gene as a cause of hereditary pancreatitis in 1996, we have seen great progress in our understanding of the genetics of pancreatitis. It has been establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 51 publications
(69 reference statements)
2
31
0
Order By: Relevance
“…Although our cohort is small, those observations are consistent with the results of a pooled case-control analysis showing that 6.2% of pdac patients have a history of pancreatitis 29 . Younger patients (<65 years of age) with a history of pancreatitis could be at increased risk for a genetic predisposition to pdac, including hereditary pancreatitis 30 . Several studies have shown that an increased body mass index (bmi) is associated with pdac risk 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although our cohort is small, those observations are consistent with the results of a pooled case-control analysis showing that 6.2% of pdac patients have a history of pancreatitis 29 . Younger patients (<65 years of age) with a history of pancreatitis could be at increased risk for a genetic predisposition to pdac, including hereditary pancreatitis 30 . Several studies have shown that an increased body mass index (bmi) is associated with pdac risk 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though p.N34S was presumed to cause a loss of function, the exact mechanism of action has never been identified, as no functional defect was demonstrated for p.N34S or any of the four intronic variants associated with this haplotype (5,7,19,20,24,26). In contrast, an unambiguous loss-of-function phenotype was evident for variant c.194ϩ2TϾC (28,35,39, and references therein), the second most frequent SPINK1 mutation that affects a splice site in intron-3 and causes exon skipping with markedly reduced SPINK1 mRNA expression (19,23). This intronic mutation is in complete linkage disequilibrium (i.e., found together) with the promoter variant c.-215GϾA.…”
mentioning
confidence: 99%
“…The exocrine pancreas with its huge rate of protein synthesis is particularly vulnerable when subjected to congestion in the busy proteintrafficking lanesan inevitable consequence of pancreastasis episodes, despite the acinar cell's best efforts to compensate by endocrine rerouting of newly synthesised enzymes; removal of zymogen granules via the three-pronged strategy of centripetal dissolution, crinophagy and basolateral redirection; and down-regulation of enzyme synthesis (19,30,34,52). The close integration between oxidative, electrophilic, ER, and inflammation stress is now regarded as the basis for many chronic diseases (177) and, increasingly, for chronic pancreatitis (97,112,123).…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…The 1998 version (24) views the acinar cell as the site of mounting electrophilic stress that steadily erodes methyl (CH 3 ) and thiol (SH) -principally glutathione (GSH ) -moieties, as a result of CYP induction, concurrent exposure to a toxicant that yields RXS, and insufficiency of refurbishing micronutrients (Figure 1). A fourth factor must now be built into the equation, namely, gene mutations that might favour the cytoplasmic presence of trypsin (97): the enzyme, as also chymotrysin, is readily inhibited by GSH via SH-SS exchange (24) should it break loose of constraint by SPINK1 (serine protease inhibitor Kazal type 1) (118), but less GSH is then available for control of electrophilic / oxidative stress and other vital roles (24,30,162). The qualifying clauses help to explain why patients on CYP-inducing anticonvulsant drugs rarely develop chronic pancreatitis, or why profound electrophilic / oxidative stress but with low CYP activity in children with kwashiorkor results in painless loss of acini, not chronic pancreatitis (64).…”
Section: Electrophilic Stress Template Component Clausesmentioning
confidence: 99%
See 1 more Smart Citation